2022
DOI: 10.1021/acs.energyfuels.1c04401
|View full text |Cite
|
Sign up to set email alerts
|

CuO Nanoparticle@Polystyrene Hierarchical Porous Foam for the Effective Encapsulation of Octadecanol as a Phase Changing Thermal Energy Storage Material

Abstract: CuO nanoparticle-doped hierarchical porous polymeric frameworks can be used for shape stability of octadecanol (OD) as a phase change material (PCM) for latent heat energy storage (LHTES) applications. A hierarchical porous foam polymer was synthesized by high internal phase emulsion polymerization of styrene and divinylbenzene doped with/without CuO. The synthesized high internal phase templated polymers (PHPs) with hierarchical pores were capable of absorbing up to 75 wt % OD without seepage behavior. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Macroporous poly(High Internal Phase Emulsion) (polyHIPE) foams offer the advantages of permeable monolith structures in many fields in which transfer phenomena are important [ 1 , 2 , 3 , 4 ]. PolyHIPEs can serves as supports in adsorption processes [ 5 , 6 ], catalysis [ 7 , 8 , 9 ], tissue engineering [ 10 , 11 , 12 ], storage of gases [ 13 ] and solvents [ 14 ], thermal energy storage [ 15 , 16 , 17 ], and in the preparation of the electrode material of supercapacitors [ 18 , 19 , 20 ]. In this context, especially in recent years, the use of polyHIPEs as support materials for preparing composite phase change materials (PCMs) has become a research topic of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroporous poly(High Internal Phase Emulsion) (polyHIPE) foams offer the advantages of permeable monolith structures in many fields in which transfer phenomena are important [ 1 , 2 , 3 , 4 ]. PolyHIPEs can serves as supports in adsorption processes [ 5 , 6 ], catalysis [ 7 , 8 , 9 ], tissue engineering [ 10 , 11 , 12 ], storage of gases [ 13 ] and solvents [ 14 ], thermal energy storage [ 15 , 16 , 17 ], and in the preparation of the electrode material of supercapacitors [ 18 , 19 , 20 ]. In this context, especially in recent years, the use of polyHIPEs as support materials for preparing composite phase change materials (PCMs) has become a research topic of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, especially in recent years, the use of polyHIPEs as support materials for preparing composite phase change materials (PCMs) has become a research topic of great interest. Several groups have reported polyHIPE/PCM composites for latent heat storage applications [ 15 , 16 , 17 , 21 ]. Studies on polyHIPE/PCM composites have reported monolithic polyHIPEs displaying leak-tightness properties during phase changes [ 15 , 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation